Letter from G.M. Pettit to James Curtis Booth, May 20, 1853 - Pettit, G. M. (1853)
Contains a list of names to be considered for potential employment at the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; Mint of the United States; United States Mint